Chlorhexidine varnishes effectively inhibit Porphyromonas gingivalis and Streptococcus mutans - An in vivo study - George Ashwin; Kalangi Suresh; Vasudevan Mithuna; Krishnaswamy N (Wolters Kluwer Medknow Publications, 2010)
Background: Chlorhexidine varnish (Cervitec- Ivoclar Vivadent- Liechtenstein) is a sustained-release delivery system that can provide protection against white spots and gingivitis, which are common iatrogenic side effects of orthodontic treatment. Chlorhexidine in varnish form does not depend on patient compliance, does not stain teeth or alter taste sensation like the mouth rinse. Materials and Methods : A split-mouth technique was followed in the treatment of 30 patients selected by stringent selection criteria, evaluating a single application of the test varnish on two randomly allotted quadrants along with a placebo on the other two quadrants. Streptococcus mutans counts responsible for white spots and P. gingivalis count [using PCR test] responsible for gingivitis were done at the start of the study, and then 1 and 3 months later. Results: The chlorhexidine varnish reduced the Streptococci mutans count at the end of 1 month, and this reduction was statistically significant. At the end of 3 months, there was no difference in the S. mutans counts between the two groups. There was a statistically significant reduction in the P. gingivalis count at the end of both 1 and 3 months in comparison to the placebo group. Conclusion: Chlorhexidine varnishes are capable of reducing S. mutans and P. gingivalis and gingivitis, thus improving the overall oral health of the patient. The side effects of chlorhexidine mouth rinses are not seen with this varnish. An application schedule of at least once a month is recommended as the effectiveness is reduced comparatively at the end of 3 months.